Recycling the domestic copper scrap to address the China’s copper sustainability - Shuo Liu; Yuanbo Zhang; Zijian Su; Manman Lu; Foquan Gu; Jicheng Liu; Tao Jiang (Journal of Materials Research and Technology, 2020)
The Chinese economy is in a critical period of continuous transformation of new and old kinetic energy and economic transformation and upgrading. Copper, the second largest strategic raw material, is still central to China’s economic development. As the major producer and consumer of electrical and electronic equipment (EEE), China’s production and consumption of refined copper is the largest in the world. Thus, it is necessary to forecast the supply and demand of China’s future copper. There is a huge gap between copper production and consumption in China, the current identified copper resources cannot meet copper consumption in the next five years, thus the import of copper will be more crucial for China’s future copper industry. Due to trade frictions, restriction on imports and other reasons, the import of copper from other countries will exist a lot of uncertainties. Hence, the domestic copper waste and scraps could be the suitable secondary resource for recycling copper in China. According to the grade and value of copper scraps, establishing quality standards and optimizing the disassembly process of the domestic Cu-bearing waste & scraps, and using the suitable method are the key to recycling the domestic copper scraps.